RELIGION AND RELIGIOUSNESS; A CLARIFICATION FOR EMPATHY - Muhamad Arfan; Iqbal Bafadal (Universitas Islam Negeri Mataram, 2024)
The nature of religion has been endlessly discussed by philosophers, theologians, psychologists, and sociologists. They look at different aspects of religion as their interests and their purposes differ. Therefore, they formulate various definitions of religion. Religion is seen to be difficult to define. But it is necessary to have a clear definition of religion as a starting point for religious studies. This paper discusses the definition of religion given by the schoolchildren and then gives a clear definition as an attempt to build up tolerance. Religion is not the same as religious beliefs and practices or religious experiences.